Low‐Cost and Scalable Ni‐Prussian Blue Analogue//Functionalized Carbon Based Na‐Ion Systems for all Climate Operations. Issue 4 (22nd November 2022) - Naskar, Pappu; Debnath, Subhrajyoti; Maiti, Apurba; Biswas, Biplab; Banerjee, Anjan
Abstract: Herein, we have developed a sodium ion based aqueous energy storage device with nickel prussian‐blue‐analogue (Ni‐PBA) positive and functionalized carbon‐black negative electrodes in 1 M Na2 SO4 electrolyte solution. The components required to develop the device, i. e ., stainless steel (SS) current‐collectors, absorbent‐glass‐mat separator, electrolyte, carbon‐black, and precursors of Ni‐PBA, are all environmentally benign and inexpensive. To minimize the corrosion of pristine‐SS, polyaniline coating on the SS surface is applied by in situ electrodeposition method. The full cell exhibits a specific capacity of 28 mAh g −1 with 90 % Coulomb efficiency (@0.2C), an energy density of 34 Wh kg −1 (@20 W kg −1 ), a power density of 100 W kg −1 (@18 Wh kg −1 ) and a good life cycle (70 % capacity‐retention over 500 cycles @1.0C rate) within the 0–1.2 V window. The cell performance is further tested under variable temperatures, and 0–50 °C range is reported to be the working window for this cell. Abstract : A low cost aqueous sodium ion battery with Na2 NiFe(CN)6 positive and funtionalized carbon negative electrodes provides reliable electrochemical performance within a temperature range of 0–50 °C.